Safety of Early Rescue Surfactant Replacement Therapy for Preterm Neonates with Respiratory Distress Syndrome at Neonatal Intensive Care Unit of a Tertiary Hospital - Yadav, Sunil Kumar; Giri, Arun (Journal of Nepal Paediatric Society, 2019)
Introduction: Respiratory distress syndrome (RDS) is an acute disease of preterm neonates and is caused by the deficiency of pulmonary surfactant. Surfactant deficiency can lead to alveolar collapse, atelectasis, impaired gas exchange, severe hypoxia and acidosis. Surfactant replacement therapy (SRT) is an integral part of management of preterm neonates with respiratory distress syndrome. The objective of the study was to evaluate the safety of early rescue surfactant replacement therapy in RDS. Methods: This was a prospective observational study conducted in a 17 bedded teaching and referral NICU of Eastern Nepal over a period of seven months. All preterm neonates with clinical and radiological features of RDS were enrolled in the study. The safety of early rescue SRT was evaluated by measuring the outcomes: incidence of pulmonary haemorrhage, apnea, hypoxia and cardiac arrest. All data were entered into the worksheet of SPSS software version (19.0) and descriptive statistics including percentages and frequencies was analysed. The level of statistical significance adopted was p-value < 0.05. Results: The survival rate of preterm babies with SRT was 64.7% (22 babies). The incidence / prevalence of pulmonary haemorrhage, apnea, hypoxia, and cardiac arrest during or immediately after SRT was 14.7%, 5.9%, 5.9% and 2.9% respectively. Conclusions: This study suggests that SRT is an effective, safe and feasible intervention in level-3 neonatal units and has the potential to reduce neonatal mortality. The study also emphasises on the fact that SRT should be provided in settings where there is adequate manpower, professional skills and desired infrastructure to administer surfactant.